2020
DOI: 10.1002/celc.202000275
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Formation of Cinnamaldehyde by the Electrolyte System N,N‐Diisopropylethylamine and 1,1,1,3,3,3‐Hexafluoropropan‐2‐ol

Abstract: The use of a supporting electrolyte has been a significant issue in electro‐organic chemistry because it can be wasteful and increase steps in terms of separation from target products. However, it is ideal for an electrolyte to play multiple roles in reactions, for example, as a feedstock or catalyst. We have discovered that the combination of N,N‐diisopropylethylamine (DIPEA) and 1,1,1,3,3‐hexafluoropropan‐2‐ol (HFIP) not only works as an electrolyte but also facilitates the electrochemical formation of cinna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…The excited state potential E( S1* / S1− ) was estimated to be 1.15 V vs. Ag/AgCl ( S1 's E 0–0 = 2.9 eV; E pc ( S1 / S1− ) = −1.75 V), which is higher than the reported potential of E (DIPEA˙ + /DIPEA) (0.9 V vs. Ag/AgCl). 37 Therefore, upon excitation, S1 attains a triplet excited state, which accepts an electron from DIPEA to give one-electron reduced S1 ( Scheme 2 , species B) and DIPEA˙ + . (7) In situ formation of electron donor–acceptor complexes is another strategy for light-induced C–Cl bond activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excited state potential E( S1* / S1− ) was estimated to be 1.15 V vs. Ag/AgCl ( S1 's E 0–0 = 2.9 eV; E pc ( S1 / S1− ) = −1.75 V), which is higher than the reported potential of E (DIPEA˙ + /DIPEA) (0.9 V vs. Ag/AgCl). 37 Therefore, upon excitation, S1 attains a triplet excited state, which accepts an electron from DIPEA to give one-electron reduced S1 ( Scheme 2 , species B) and DIPEA˙ + . (7) In situ formation of electron donor–acceptor complexes is another strategy for light-induced C–Cl bond activation.…”
Section: Resultsmentioning
confidence: 99%
“…The excited state potential E(S1*/S1 -) was estimated as 1.15 V vs Ag/AgCl (S1's E 0-0 = 2.9 eV; E pc (S1/ S1 -) = -1.75 V), which is higher than the reported potential of E(DIPEA •+ /DIPEA) (0.9 V vs Ag/AgCl). 37 shows an intense absorption at 250-300 and weak absorption beyond 325 nm. For indole substrate S1 (0.1 M), there is an intense absorption at 250-330 nm, with absorption tail ending at ~390 nm (Figure S11).…”
Section: Articlementioning
confidence: 99%
“…The Chiba group recently identified a novel mode of reactivity and reported a HFIP/DIPEA‐based aldol reaction, whereby the ethyl group of DIPEA additionally serves as a C 2 source . Mechanistic studies revealed that DIPEA and HFIP play a significant role within this reaction.…”
Section: Anodic Formation Of Cinnamaldehydes With Dipea As Reagentmentioning
confidence: 99%
“…[35] Many more seminal applications of this powerful combination have been recently published and will be discussed within this review. [36][37][38][39][40]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation